Development of TPACK Assessment Instruments and Lesson Plan on OBE Integrated with Islamic Values and Local Culture in Mathematics Learning Planning Courses - Noviarni, Noviarni; Hasibuan, Ismail Mulia; Amelia, Rizki (JRPM (Jurnal Review Pembelajaran Matematika), 2025)
Thi study aims to describe the results of the development of lecture tools for Integrated Islamic Values ​​and Local Culture of Mathematics Learning Planning, in the form of TPACK Assessment Instruments and OBE-Based RPS. The research employed a development approach using the Plomp model, consisting of the preliminary design, experimental design, and perspective analysis stages. Data was collected through questionnaires and semester examination tests and analyzed using quantitative and qualitative descriptive methods. The results show that the OBE-based TPACK and RPS assessment instruments are classified as very valid, with a validity score of 92.24. Small-group trials indicated the tools were practical (76.39), while limited-group trials showed they were very practical (89.42). The effectiveness test revealed that the developed product was effective, with a t-value of 9.465 exceeding the t-table value of 2.004. Students who used the developed lecture tools achieved higher average scores (84.07) than those who did not (74.18). These findings indicate that the developed tools effectively facilitate mathematics learning planning courses for mathematics education students at UIN Suska Riau.